Effects of irrigation and organic fertilizer on pumpkin yield, quality, and water-fertilizer use efficiency in arid northwest China - Meng Yin; Jinxia Zhang; Liangliang Du; Lin Ding; Tao Zhong; Pengliang Tian; Runheng Yang (Frontiers in Plant Science)
Due to the increasing water scarcity and the need for sustainable agricultural practices in arid regions, optimizing water and fertilizer management is crucial for enhancing crop productivity and resource efficiency. Field experiments in 2022 and 2023 in northwestern China’s arid region explored the impacts of irrigation volume, organic fertilizer use, and their coupling on pumpkin yield, quality, and water-fertilizer efficiency. The study included ten treatments with a completely randomized two-factor design, comprising three irrigation quotas, three organic fertilizer application rates and a control group (CK). The results showed that the organic fertilizer application significantly enhanced soil moisture content, which peaked at a depth of 50 cm. Irrigation quota and organic fertilizer application had a highly significant impact on pumpkin vine length and stem diameter (P < 0.01), with a significant interaction between the two factors (P < 0.05). The rate of dry matter accumulation in pumpkin peaked at 60 ~ 80 days after sowing, with a trend of F2 > F3 > F1 in dry matter accumulation at identical irrigation quota. The effects of irrigation volume, organic fertilizer application and water-fertilizer coupling on pumpkin yield, irrigation water use efficiency (IWUE), partial fertilizer productivity (PFP) and pumpkin quality were statistically highly significant (P < 0.01). Specifically, increasing the irrigation volume from W1 to W3 increased the yield by 17.36%. However, pumpkin yield initially increased and then decreased in response to increasing organic fertilizer application. IWUE increased and then decreased with the increase of organic fertilizer application, while PFP increased with the increase of irrigation volume. Regression analysis revealed that the optimal range for irrigation quota to ensure pumpkin quality was 430 ~ 506 m3·ha-1, and that for organic fertilizer application was 5,373 ~ 6,570 kg·ha-1. When only quality indicators were considered, the W2F2 treatment performed well. However, from the comprehensive evaluation of pumpkin yield, quality, and water and fertilizer use efficiency using the TOPSIS method, the W3F2 treatment was identified as the most suitable among the water- fertilizer coupling management modes considered in this study for pumpkin cultivation in the arid northwestern China.